Making teamwork work: enhancing teamwork and assessment in higher education - Nigel Francis; Connie Pritchard; Zoe Prytherch; Stephen Rutherford (FEBS Open Bio)
The ability to work in teams is one of the most sought‐after graduate skills by employers. However, team‐based learning activities, and especially team‐based assessments, are commonly disliked (even actively avoided) by students. Team‐based assessments are often problematic for students, mostly due to logistical problems and interpersonal difficulties. These difficulties often lead to dissatisfaction with the process and poor satisfaction responses in quality assessments of their teaching. This review takes a four‐way approach to evaluate current approaches to team assessment aimed at enhancing student engagement, satisfaction and learning gain. Firstly, we identify why team‐based activity is so important to include in our overall pedagogy in Higher Education. Secondly, we examine evidence from the literature on students' reactions to team‐based activities (especially focusing on assessment) and the reasons for both positive and negative perceptions. The third focus is on identifying the root of the problem from a pedagogic perspective and highlighting the deficiencies in approaches to team‐based activities that might lead to negative student perceptions. Finally, we discuss examples from the literature of where team‐based learning and assessment activities have been successful. Approaches to team‐based activities need to be more proactive and supportive so that students understand the dynamics of teams, how to plan team‐based activities, and how to deal with interpersonal issues positively and productively. Team‐based learning is arguably the least well‐taught element of our curricula, yet it is important and straightforward to address.